2021
DOI: 10.18502/fbt.v8i1.5860
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Activation Changes Associated with Autonomous Sensory Meridian Response (ASMR): Initial Case Report

Abstract: The Autonomous Sensory Meridian Response (ASMR) is a unique phenomenon to provoke a sense of relaxation that has been proposed for a few years. This phenomenon suggests acoustic-visual stimuli  for cultivating a peaceful environment for the mind as well as a tingling sensation. Some studies suggest that this phenomenon is comparable with mindfulness; surprisingly, published articles in this regard are growing increasingly to examine how it happens scientifically. Some studies have been done on neuroimaging tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…K. Fredborg et al, 2021; M. Lee et al, 2019; Paszkiel et al, 2020; Pedrini et al, 2021; Seifzadeh et al, 2021; Swart, Banissy, et al, 2022; Tian et al, 2020) and fMRI studies (seven studies, S. Lee et al, 2020; Lochte et al, 2018; Sakurai et al, 2021; S.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…K. Fredborg et al, 2021; M. Lee et al, 2019; Paszkiel et al, 2020; Pedrini et al, 2021; Seifzadeh et al, 2021; Swart, Banissy, et al, 2022; Tian et al, 2020) and fMRI studies (seven studies, S. Lee et al, 2020; Lochte et al, 2018; Sakurai et al, 2021; S.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al, 2019; Paszkiel et al, 2020; Pedrini et al, 2021; Seifzadeh et al, 2021; Swart, Banissy, et al, 2022; Tian et al, 2020). The previously mentioned studies by Tian et al (2020) and Seifzadeh et al (2021) involving very small sample sizes reveal a significant α increase post-ASMR versus resting state (Seifzadeh et al, 2021, especially in the central region). However, Seifzadeh et al (2021) also report an α band power decrease in the occipital region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was statistically shown that ASMR effectively reduced the state anxiety of the participants, considering the subjectivity of the “questionnaire report,” the practice effect of the design before and after the test, as well as the influence of psychological comfort and other factors, the significant effect may be exaggerated. In general, ASMR is a unique form of relaxation that uses auditory and visual stimuli to bring about a calm state of mind and tingling sensations, like mindfulness (Seifzadeh et al., 2021 ). Some studies have shown that ASMR has the same characteristic factors as mindfulness training (Fredborg et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This did not seem to occur in control participants. Seifzadeh et al [14] examined the variations in EEG frequency bands in pre-ASMR versus post-ASMR [14]. Finally, Koo et al [15] found that arousal was a key feature of ASMR [15].…”
Section: Introductionmentioning
confidence: 99%